Avaliação da radioatividade natural do Granito Madeira - região norte do Amazonas: região norte do Amazonas - Vanderlei Vilaça de Moura (2017)
To evaluate the natural background radiation, an area was selected in the northern part of the State of Amazonas. It is the Granite Madeira, located inside a mining NORM (Naturally Occurring Radioactive Materials) mining company that extracts ores with natural uraniumand thorium. The equipment used was a sodium iodide scintillator calibrated with a source of Cs-137 and measured with zirconite zirconium ore with associated natural uranium and thorium. Due to the extension of the Granito Madeira (60 km2) and the difficulty of access,since it is an area covered by forest in almost totality, 14 representative areas were selected, comprising: survey areas; Areas close to sites explored in the past; Areas without anthropogenic action. The data obtained by the scintillator were classified, georeferenced and treated using the GARM (Geolocation Application for Radiation Monitoring) and QGis (Quantum Gis) softwares with the objective of representing the environmental dose equivalent rates in maps, tables and frequency histograms. Subsequently, dose rates were used to obtain the the annual dose relative to gamma radiation in Granito Madeira. These data wererepresented in frequency histograms, tables and maps with level curves and isodose by Surfer software. The mean values obtained were: 0.7 + 0.4 uSv.h-1, for the ambient dose equivalent rate; And 6.0 + 3.0 mSv for the annual dose relative to gamma radiation. The results of this study were compared with that of other authors and UNSCEAR, 2010 (United Nations Scientific Committee on the Effects of Atomic Radiation) where it was verified that the natural radioactivity of the bottom of the Madeira Granite is superior to the world average, being superior Even from other areas with NORM material.